Genetic Algorithm Based Handwritten Numeric Strings Recognition - Shahed, Maytham A. (Basrah Journal for Engineering Sciences, 2010)
This paper presents an approach for the recognition of off-line handwritten numeric strings using genetic algorithm. The proposed scheme is divided in two parts. The first part is remove the image noise, then the vertical projection is used to segment the numeric strings at isolated digits and every digit will be presented separately to the second part. The second part using improved genetic algori_thm to recognize isolated handwritten digit. The result of the recognition of the numeric strings will display at the exit of the global system.